Supervisi Klinis untuk Meningkatkan Keterampilan Guru - Betaria Betaria; Anelvi Izatul Hanifa; Merissa Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Clinical approach or clinical supervision assumes that the teacher's learning process to develop is always related to the teacher's own individual learning process. The clinical approach is a face-to-face process between the supervisor and the teacher. This meeting discusses teaching problems and those related to it. Therefore, in clinical supervision, the supervisor and teacher act as colleagues in solving learning problems. For different types of teachers, the supervisor must also distinguish the types of clinical supervision strategies that will be used. The type of professional teacher is suitable for using non-directive strategies, the type of critical teacher and busy teacher can use collaborative strategies. Meanwhile, for teachers who are not qualified, supervisors are expected to be more active in guiding and teaching these teachers, so that the right strategy is direct clinical supervision.